Hydrocarbon Pollution and Potential Ecological Risk of Heavy Metals in the Sediments of the Oturuba Creek, Niger Delta, Nigeria - Ezekwe, Clinton Ifeanyichukwu; Utong, Israel Clinton (Journal of Environmental Geography, 2017)
This study aimed at examining the impact of oil pollution from artisanal oil refineries on the Oturuba river ecosystem using active river bottom sediment. Specific objectives included to determine the level of hydrocarbons and trace metals (Pb, Cd, Zn, Cu, Ni, V and Mg) in the sediments and to relate this with general ecosystem health. The study found elevated concentrations of both hydrocarbons and heavy metals in the range above most sediment quality guidelines exceeding the respective Threshold Effects Level and Probable Effects. Level guideline values and occurring at levels where impairment to biological communities is certain an d where toxicity levels can lead to negative impacts on benthic animals or infaunal communities. Heavy metal geochemical accumulation index and potential ecological risk analysis also returned anomalously high concentrations in the range of very highly polluted sediment environments with very high ecological risk indices, thereby ranking the Oturuba Creek as one of the most polluted coastal river systems in the world.